Using a proforma to improve standards of documentation of an orthopaedic post-take ward round. Issue 1 (24th April 2013) - Duxbury, Oliver; Hili, Stephanie; Afolayan, John
Abstract: In Trauma and Orthopaedics, a daily Trauma Meeting (TM) occurs, where the previous 24-hour take is discussed and a management plan is decided by the consultant on-take. The post-take ward-round (PTWR) usually follows. In the district general hospital (DGH) where this audit was conducted, clinical incidents and root-cause analysis revealed that the TM/PTWR documentation were suboptimal. We identified gold standards. Variables included clear documentation of PTWR, date/time, consultant on-take, clinician leading the ward-round, and management plan. 50 cases were reviewed retrospectively. 72% were seen on PTWR. 47% of these were clearly labeled PTWR. 64% of the cases not seen on PTWR were weekend admissions. Documentation of the previously mentioned fields were also poor. Audit results were presented at the department meeting and a Trauma Meeting/Post-Take Ward Round Proforma was implemented. A prospective re-audit of 50 cases revealed that patients not seen on a PTWR decreased to 18%; 4% of these were weekend admissions. 88% of patients seen had a proforma completed. 18% of all cases did not have a proforma. Introduction of the proforma established a system to document discussions at the TM and improved the quality of documentation of the consultant-led plans. Such a simple tool can improve the overall care of patients and potentially protect staff.